Protest cycles and democracy in Portugal, 2000–2019 - Fernandes, T.; Araújo, C. (After the carnations: Social movements in Portugal since the 25 April 1974 revolution, 2025)
Since the global protest wave of the 1960s-1970s, the sphere of collective action became a common subsystem of modern democratic regimes, alongside conventional representative institutions, such as elections, parliaments or bodies of state-interest group consultation (e.g., pluralist or corporatist) (Dolenec, 2017; Dolenec at al. 2020; Ekiert and Kubik, 2001; Schmitter, 1981; Schmitter 1999). Democratic regimes have since come to accept practices such as demonstrations and strikes as legitimate and even desirable, and, although at varying levels, even to tolerate disruptive protest repertoires such as occupations. Furthermore, it has been recognized by both scholars and political actors that participation in street politics through protest is often aligned with conventional political participation, such as voting. Not only do participants in popular mobilisation tend to vote more frequently, but elections also function as an opportunity for social movements to draw attention to their claims. Both arenas have become mutually reinforcing, thus contributing to increasing citizens' civic competences and the legitimacy of democratic regimes (Tarrow, 2011; della Porta, 2013, pp. 57-59).